Mekanisme Tanggung Jawab Pers Atau Media yang Menyebarkan Berita Bohong atau Informasi Menyesatkan Selama Masa Pemilu - Prasetiyo, Ricy Budiman; H, Hufron (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The spread of fake news or hoaxes through mass media, particularly during election periods, can potentially disrupt public order and undermine the integrity of democracy. This study aims to examine the forms of legal protection governing the responsibilities of the press in preventing the spread of fake news in Indonesia. The method used is a normative juridical approach by studying statutory regulations and related documents. Study results show that legal protection against the spread of fake news has been regulated through several legal instruments, among them the Law Number 40 of 1999 on the Press which guarantees the freedom of the press yet obliges the presentation of accurate and non-misleading information; the Journalism Code of Ethics which governs the standards of journalistic work ethics; as well as provisions in the Information and Electronic Transactions Act (UU ITE) and the Criminal Law Book (Criminal Code) that provide a criminal basis for the dissemination of fake news causing trouble. Additionally, the Press Council plays a role in providing legal protection through press dispute resolution mechanisms as well as education towards the media. These legal protections are not only repressive through sanctions, but also preventive through ethical regulation and institutional oversight. Thus, the responsibility of the press in preventing fake news is not only anchored on the principle of freedom, but also subject to legal corridors in the public interest.